A brief overview of smallholder farmers' access to seed of improved legume varieties - Akpo, E.; Ojiewo, Christopher Ochieng; Omoigui, L.O.; Rubyogo, Jean-Claude; Varshney, Rajeev K. (Springer, 2020)
For decades, the vast majority of smallholder farmers in developing countries, mainly sub-Saharan Africa (SSA) and to some extent South Asia (SA), heavily rely on non-improved and auto-saved variety seed, accounting for about 80% of their material used for planting. Though the seed use figures by farmers vary from one region to another, with West Africa showing the lowest rate of improved seed use (below 20%) and South Asia with much higher rate (up to 70%), the overall situation looks less encouraging. At the same time, substantial breakthroughs have been made by breeding programs, and many more are still in the pipeline. Some of the traits of recently developed varieties have targeted the consumers’ demands and farmers’ preferences.